Serum tryptophan-kynurenine metabolites served as biomarkers of disease activity in rheumatoid arthritis and linked to immune imbalance - Ruihe Wu; Baochen Li; Rui Su; Xiaoyang Liu; Anqi Gao; Jing Luo; Chong Gao; Xiaofeng Li; Caihong Wang (Arthritis Research & Therapy)
Abstract Background Immune imbalance caused by imbalanced helper T(Th)17/regulatory T (Treg) and follicular helper T (Tfh)/follicular regulatory T (Tfr) cells drives the onset of rheumatoid arthritis (RA) fundamentally. Tryptophan (Trp) metabolism is crucial in regulating immune and altered Trp metabolism has been reported in RA. However, the potential of altered Trp metabolites to serve as RA-related biomarkers and their relationship to immune balance in RA remains undetermined. Methods We explored the Trp metabolic characteristics in RA by comparing the targeted quantitative Trp metabolomics between 29 new-onset RA patients and 19 healthy controls (HCs). The RA-related disease biomarkers from Trp metabolites were identified to construct a classification model through machine learning algorithms. Their association with immune imbalance in RA was analyzed. Results Differential analysis exhibited significant alterations in serum Trp metabolites and metabolic pathways between RA and HCs. There were 7 differential metabolites of serum Trp, which were all decreased in RA (P < 0.05). Trp metabolic pathways analysis indicated that the Trp-Kynurenine(Kyn) pathway was downregulated in RA(P < 0.05). And the key enzyme of the Trp-Kyn pathway, indoleamine-2,3-dioxygenase1 (IDO1), was reduced in RA (P < 0.05). Altered Trp metabolites especially those from the Trp-Kyn pathway exhibited a negative correlation with the clinical indicators and autoantibody expression. 4 Trp metabolites from the Trp-Kyn pathway including Trp, xanthurenic acid (XA), cinnabarinic acid (CA) and kynurenic acid (KynA) were identified as RA-related disease biomarkers to construct RA-HC classification model, which exhibited good ability to distinguish RA from HCs (AUC = 0.951, 95%CI = 0.897-1.000) and stratify disease activity of RA. In addition, these Trp-Kyn pathway metabolites were also associated with the immune imbalance of RA. Specifically, reduced Trp and XA were negatively related to the imbalanced Th17/Treg cells, and reduced KynA was negatively associated with the imbalanced Tfh/Tfr cells. And the reduced IDO1 was also negatively correlated to the imbalanced Tfh/Tfr cells. Conclusions Altered Trp-Kyn metabolism might contribute to the pathogenesis of RA. We highlighted the association of the Trp-Kyn metabolic pathway with immune imbalance in RA and its potential value in clinical practice, particularly in early diagnosis, disease activity monitoring, and personalized treatment.